Games board development as a media in guidance and counseling services - Meriza Netaniel; Anastasia Catur O. P.; Christina Andriyani K.; Dwi Murtiningrum (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2022)
Problems in education, with the increasingly sophisticated digital world changing the way of teaching. Website is one of the media that can be accessed by everyone and using any technology. This website is a solution for teachers to develop their creativity in developing learning methods and materials. This study aims to determine the effectiveness of providing inspiration for the use of game board websites to prospective BK teachers to be used in the learning process at school. While the purpose of the media that we created is to provide facilities for BK teachers in learning media for teacher creativity. Subjects taken are based on prospective BK teachers. The method used is research and development. In this study, the researcher went directly to the field to make observations, interviews and documenting activities as well as providing a questionnaire via the g-form. The results showed that there was (1) an increase in teacher interest in using learning media as an effective method of delivering material, (2) the application of the website was easy and practical, (3) it was admitted that it was easy to implement the BK program. In addition, there are also inhibiting factors in developing teacher creativity, namely: it requires more costs in its application and takes time to create media.